Experimental Investigation of Compressive Strength and Infiltration Rate of Pervious Concrete by Fully Reduction of Sand - Aneel Manan; Mushtaq Ahmad; Fawad Ahmad; Abdul Basit; Muhammad Nasir Ayaz Khan (Salehan Institute of Higher Education, 2018)
The aim of the study is to investigate compressive strength of pervious concrete by reduction of fine aggregate from zero to 100%, additionally investigate infiltration rate of pervious concrete. Experimental study has conducted at Cecos Engineering University Peshawar. The pervious concrete samples were produced for 7 and 28 days. Compressive strength of pervious concrete indicated higher reduction of the sand reduces compressive strength and almost 50% compressive strength decreased by reduction of 100% sand from the design mix. On the other side, infiltration rate for 28 days shows direct relation above 40% reduction of sand and highest 273% of infiltration rate by reducing 100% sand from the design mix. The 90% reduction of sand from concrete give considerable compressive strength of 2150 psi and infiltration rate of 165.79 inch/hour, which can be recommended for pavements of parking and walking area.